Общественно-патриотическая деятельность армянской интеллигенции России в годы Геноцида - Роберт Багдасарян (ՀՀ ԳԱԱ հրատ.)
Ռուսահայ հասարակական-քաղաքական ու գրական մշակութային առավել հայտնի գործիչներ Ալեքսեյ Ջիվելեգովը, Գրիգոր Չալխուշյանը, Կարեն Միքայելյանը իրենց հասարակական-հայրենասիրական գործունեության մեջ մշտապես հետևել և ուշադրության կենտրոնում են պահել հայերի պատմական ճակատագրի հարցը, հայ ժողովրդի նորագույն պատմության ողբերգական էջերը, մասնավորապես Հայոց ցեղասպանությունը: More known socio-political and literary cultural figures of Armenians of Russia Alexey Jivelegov, Grigor Chalkhushyan, Karen Mikayelyan have always followed in their socio-patriotic activities and kept in the centre of attention the issue of historical fate of the Armenians, the tragic pages of the newest history of the Armenians, particularly the Armenian Genocide.
Keywords: History; Armenian Genocide (1915); D History